Understanding the Societal Roots of Pak-KSA Defence Ties: A Historical Analysis - Hussain, Tasawar; Younus, Aisha (Regional Lens, 2025)
In the backdrop of recent Israel war on Gaza, world has witnessed extraordinarily close relationship between Pakistan and the Kingdom of Saudi Arabia. Against this pretext, the relevance of social factors in the making of strategic ties is important to understand what has constituted the special ties between two states (Guzansky, 2016). It demands that we should make a clear understanding of these constituents in international and bilateral relations. The present study constitutes a significant addition to the theoretical knowledge existing in the literature relating to bilateral relationship between Kingdom of Saudi Arabia and Pakistan. It argues that interaction between the definition of “self” and ‘other’ determine a state to formulate policy about other state as friend, ally or adversary. Similarly, it is the conservative religion-cultural self-identity and mutual definition of Pakistan and Saudi Arabia that help articulate their policy towards each other. Such an ideological affinity provides both sates a strong foundation to further consolidate their bilateral ties in all possible areas of cooperation including the military one.